Critical re‐evaluation of Limulidae uncovers limited Limulus diversity. (2nd March 2021) - Bicknell, Russell D. C.; Błażejowski, Błażej; Wings, Oliver; Hitij, Tomaž; Botton, Mark L.
Abstract: Horseshoe crabs are archetypal marine chelicerates with an exceptionally long fossil record. Due to the historical nature of the genus Limulus, which extends back to Linnaeus' descriptions, many horseshoe crab fossils were traditionally placed in Limulus and the family Limulidae. Despite continued research into the accurate placement of species within Limulidae, a systematic outline of characteristics that define limulid genera, specifically using exclusively dorsal characteristics, does not yet exist. However, such an approach is essential as appendage data is rarely preserved in fossil horseshoe crabs. Here we present a systematic review of Limulidae with a focus on dorsal features, and illustrate all accepted limulid species across the 12 genera. Through this descriptive lens, we consider the validity of supposed Limulus species outlined in a recent xiphosurid review. We find evidence for only one fossil Limulus species: Limulus coffini . This revision therefore excludes Limulus from Jurassic‐aged deposits. We refer ' Limulus ' darwini from the Upper Jurassic (Upper Tithonian) of Poland to Crenatolimulus darwini comb. nov. and ' Limulus ' woodwardi from the Middle Jurassic (Aalenian) of England to Mesolimulus woodwardi comb. nov. This highlights that the Limulus evolutionary record is highly constrained and started as recently as the Late Cretaceous. The rare Limulus fossil record emphasizes the current need for conservation of extant species and the importance of thoroughly scrutinizing the morphology of fossil specimens to uncover all facets of the limited limulid evolutionary record.